2022
DOI: 10.1186/s12870-022-03642-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation mechanisms of flavonoids biosynthesis of Hancheng Dahongpao peels (Zanthoxylum bungeanum Maxim) at different development stages by integrated metabolomics and transcriptomics analysis

Abstract: Background Flavonoids have strong free radical scavenging and antioxidant capacity. The high abundance of flavonoids in Chinese prickly ash peels have many benefits to human health. In this study, ‘Hancheng Dahongpao’, a main cultivar, was taken as materials to investigate the flavonoids biosynthesis mechanism of Zanthoxylum bungeanum Maxim at three key development stages by integration of metabolomics and transcriptomics analysis. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…They suggested that the MYC2, NAC71, WRKY57, and TCP7 TFs might be participated in the regulation of anthocyanin structural genes. Similarly, Zheng et al (2022) found that the UFGT gene and two ANS genes were upregulated in the whole developmental stages of Zanthoxylum bungeanum fruit peels, which may represent key functional genes for the accumulation of peonidin 3-O-glucoside and peonidin Ohexoside. Therefore, multiomics analysis is a powerful strategy to explore the regulation of the anthocyanin network at different developmental stages in plants (Liu et al, 2017;Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…They suggested that the MYC2, NAC71, WRKY57, and TCP7 TFs might be participated in the regulation of anthocyanin structural genes. Similarly, Zheng et al (2022) found that the UFGT gene and two ANS genes were upregulated in the whole developmental stages of Zanthoxylum bungeanum fruit peels, which may represent key functional genes for the accumulation of peonidin 3-O-glucoside and peonidin Ohexoside. Therefore, multiomics analysis is a powerful strategy to explore the regulation of the anthocyanin network at different developmental stages in plants (Liu et al, 2017;Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…In flowering plants, the color changes that occur in floral organs are closely related to anthocyanins ( Shen et al., 2021 ). Thus far, several genes involved in the anthocyanin biosynthesis pathway have been identified in most plants ( Boss et al., 1996 ; Saito et al., 2013 ; Zheng et al., 2022 ). These genes mainly include dihydroflavonol 4-reductase (DFR), anthocyanidin synthase (ANS), and UDP-glucose: flavonoid 3-glucosyltransferase (UFGT) ( Schaart et al., 2013 ; Wang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated using the Trizol Reagent (Invitrogen Life Technologies, Shanghai, China), and 3 μg RNA was used as input material for the RNA sample preparations. The total RNA was quantified, and the quality was assessed using an Agilent 2100 Bioanalyzer system (Agilent Technologies, Palo Alto, CA, USA) [ 68 ]. The sequencing library was sequenced on NovaSeq 6000 platform (Illumina) by Personal Biotechnology Cp., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Zanthoxylum bungeanum Maxim., known as Chinese prickly ash, is widely distributed in China and was the most important, traditional condiment and medicinal plant in China for hundreds of years and has strong ecological adaptation [ 1 , 2 , 3 ]. Due to the influence of other species, geographical conditions, climate factors and chemical composition, the color of Chinese prickly ash peel produced in different regions is different [ 4 ].…”
Section: Introductionmentioning
confidence: 99%